INFORMASI DETEKSI SUMBERDAYA AIR TANAH ANTARA SUNGAI PROGO – SERANG, KABUPATEN KULON PROGO DENGAN METODE GEOLISTRIK - Agung Riyadi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2004)
The demand for groundwater in developing countries is continuously increasing. It is used as industrial processes, drinking, agriculture, fishpond and irrigation. The reasons for this growth include agriculture, industrial processes, expanding cities, food production needed irrigation areas that urgently need groundwater supply. Actually now, in south Kulon Progo coast area, many people development agriculture with water supply from groundwater. From the measurement in the field concerning groundwater resources potential in thesouth Kulon Progo coast area, can be predicted that the fresh water resources be found as far as coast from Serang River until Progo River, with average wide 1.6 km and thick between 20 – 43 meter and with depth average 25 meter.